ENVIRONMENTAL SAFETY IN THE CONSTRUCTION OF INDUSTRIAL AND RESIDENTIAL BUILDINGS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article attempts to briefly discuss environmental issues in the construction industry. The construction industry currently accounts for 40% of global energy consumption and is expected to grow in the coming years. This is not hard to believe when you consider the number of buildings that grow every day. It takes a lot of components to make a building come to life for everything to work. Starting from excavation in search of raw materials like limestone and ending with the extraction of water. In fact, everything you see in a building requires a certain amount of energy to transform into a usable form. The result is ever-increasing pollution of the environment.